ANALISIS DNA TURUNAN GENERATIF JATI (TECTONA GRANDIS U) DENGAN METODA RANDOM AMPLIFIED POLYMORPHIC DNA - Cintamulya, Imas
Abstrack The DNA analysis was carried out to evaluate progenies of teak trees by using the RAPD (Random Amplified Polymorphic DNA) method. The analysis was done to compare progenies and their parentals of teak at the DNA level. DNA samples were isolated from the \"plus\" teak trees (No.24 and 30) and their progenies. DNA samples were amplified by using 7 different nucleotide decamer primers and separated by electrophoresis on 1.4% agarose gels. \"Simple Matching\" equation was used to determine similarity coefficient between progenies and their parentals. A dendogram was constructed based on the matrix data by applying unweighted pair-group method with arithmetic averages (UPGMA). The result showed that there were 114 DNA bands ranged between 200-3610 bp. There were three specific bands of 460, 640 and 1400 bp in size from DNA samples of \"plus\" teak trees No. 24 and their progenies. There was no specific band from DNA samples of \"plus\" teak trees No. 30 and their progenies. Similarity coefficient of \"plus\" teak trees No. 24 and their progenies ranged between 0,58-0,84 and \"plus\" teak trees No. 30 and their progenies ranged between 0,62-0,86. The result of cluster analysis showed that there were two main groups of the family of each \"plus\" teak tree and its progenies. One group is the group of progenies and the other group is the parental. The experimental results indicated that, at the DNA level, progenies of \"plus\" teak trees were not always the same, genetically, compared to their parentals. And so, among progenies from the same \"plus\" teak trees showed a genetic diversity.